Strategi Penghimpunan Zakat di Era Digital: Peran Lembaga, Pemerintah, dan Inovasi Teknologi - Maulana, Akhmad Ferindra (Maliki Interdisciplinary Journal, 2025)
Zakat collection is a fundamental element in the Islamic financial system that aims to redistribute wealth and improve social welfare. This article discusses the factors that influence the success of zakat collection, methods of collecting zakat (direct and indirect), and the role of government and private sector in optimizing its management. In Syafi'iyah fiqh, the collection of zakat by official institutions such as BAZNAS and LAZ is allowed and supported by Qur'anic arguments. Technological advances have also encouraged innovation in zakat collection through digital platforms, e-wallets, payroll systems, and QR codes, which facilitate payments and increase the efficiency of zakat fund distribution. In addition, digital marketing strategies and financial transparency are important factors in increasing public trust in zakat institutions. This research uses descriptive-qualitative approach with literature study method that analyzes various policies, best practices, and challenges in zakat collection in Indonesia. The results of this study are expected to provide insights for zakat institutions in developing a more effective and sustainable collection strategy.